2014
DOI: 10.1038/eye.2014.46
|View full text |Cite
|
Sign up to set email alerts
|

Retinal nerve fiber layer evaluation of spectral domain optical coherence tomograph and scanning laser polarimeter to diagnose glaucoma

Abstract: Purpose To compare the abilities of retinal nerve fiber layer (RNFL) parameters of spectral domain optical coherence tomograph (SDOCT) and scanning laser polarimeter (GDx enhanced corneal compensation; ECC) in detecting glaucoma. Methods In a cross-sectional study, 215 eyes of 165 subjects (106 eyes of 79 glaucoma patients and 109 eyes of 86 controls) referred by general ophthalmologists for glaucoma evaluation underwent RNFL imaging with SDOCT and GDx ECC. Ability of RNFL parameters of SDOCT to discriminate g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
(48 reference statements)
0
4
0
Order By: Relevance
“…We have earlier used such a control group for evaluating the diagnostic ability of imaging technologies in glaucoma. [16][17][18][19][20]…”
Section: Discussionmentioning
confidence: 99%
“…We have earlier used such a control group for evaluating the diagnostic ability of imaging technologies in glaucoma. [16][17][18][19][20]…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have compared the RNFL parameters of SDOCT and GDx ECC in perimetric glaucoma and have found that the diagnostic abilities were comparable [15] [17] . Garas et al [16] though had a group of preperimetric glaucoma subjects in their study, did not analyze the results separately in this subgroup.…”
Section: Discussionmentioning
confidence: 99%
“…However, in clinical practice, a diagnostic test is used to rule-in disease in very early stages (preferably in preperimetric stages of glaucoma) or rule-out disease in subjects suspected of having disease. In a previous study, we compared the diagnostic abilities of the RNFL parameters of SDOCT and GDx ECC in perimetric glaucoma and found them to be comparable [17] . However there were indications of SDOCT being better in early stages of perimetric glaucoma.…”
Section: Introductionmentioning
confidence: 95%
“… [20] We believe that including a control group which is likely to cause some amount of diagnostic uncertainty is more meaningful and mimics the real-life clinical situation than a control group with no suspicious findings of the disease as was used in the previous studies. We have earlier used such a control group for evaluating the diagnostic ability of imaging technologies in glaucoma [12] , [14] , [21] , [22] .…”
Section: Discussionmentioning
confidence: 99%